Bridging the Learning Gap: Implementing Teaching at the Right Level in Secondary School Mathematics - Sari, Vernita; Mustafa, Sriyanti; Dollo, Asdar; Ali, Ayu Rahyuni (Jurnal Pendidikan MIPA, 2025)
The study evaluates whether and to what extent the Teaching at the Right Level (TaRL) intervention improves students’ learning in mathematics across cognitive, affective, and psychomotor domains. This study employed a pre-experimental one-group pre-test/post-test design, in which a single cohort of 35 Grade XI students at Senior High School I, Takalar, South Sulawesi, Indonesia, was assessed before and after the implementation of the TaRL approach. Data were gathered using pre- and post-tests to measure cognitive improvement. The cognitive, affective, and psychomotor domains were assessed with structured observation sheets using a five-point Likert scale, which were then transformed to a 0-100 scale for clarity of interpretation. The result showed a significant increase in students’ cognitive achievement, with the pre-test and post-test means of 83.42 and 93.22, respectively. Although the initial score was relatively high due to students’ prior exposure to similar mathematical content, the statistical results confirmed a meaningful improvement beyond the baseline understanding. Observations of the affective domain revealed notable positive shifts; students demonstrated higher motivation, increased confidence in problem-solving, and more active participation during class activities, as reflected in an average converted score of 95.31. In the psychomotor domain, the mean score of 93.21 demonstrated students’ enhanced ability to apply mathematical concepts in practical contexts through active engagement. These findings suggest that the Teaching at the Right Level (TaRL) approach effectively enhances students’ learning outcomes within the studied context by promoting active, differentiated, and student-centered learning experiences. Since the study was conducted at a single institution with a small sample, additional research with larger populations and diverse educational contexts is necessary to substantiate and generalize these findings.    Keywords: affective, cognitive, mathematics, psychomotor, teaching at the right level (TaRL).